Life on the Mississippi, Part 6. - Twain, Mark, 1835-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Life on the Mississippi, Part 6." by Mark Twain is a memoir published in 1883. This work recounts Twain's experiences as a young steamboat pilot apprentice on the Mississippi River before the Civil War, followed by his return journey decades later. The book blends vivid descriptions of navigating the ever-changing river with observations on how time, railroads, and progress transformed the landscape and culture along America's great waterway. Twain mixes personal anecdotes, tall tales, and social commentary throughout. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Life_on_the_Mississippi
Release date is 2004-07-09
Produced by David Widger
Keywords: Mississippi River -- Description and travel; Mississippi River Valley -- Social life and customs -- 19th century; Authors, American -- 19th century -- Biography; Pilots and pilotage -- Mississippi River; Twain, Mark, 1835-1910 -- Travel -- Mississippi River